RED VELVET CAKE SUBTITUTION BROWN RICE FLOUR INNOVATION OF FIBER DESSERT PRODUCTS - Sugiyono, Sabilah Dwiyanti (Prosiding Pendidikan Teknik Boga Busana, 2020)
In Indonesia there are various types of cereals with various colors, varieties and shapes, which are potentially potential to add variety and nutrients in various patriotic products. Brown rice is a type of rice (Oryza sativa L.) with high anthocyanin content so that the red color of rice contains more components of nutrients and non-nutrients such as dietary fiber, phytic acid. vitamin E and vitamin B and Î³-aminobutyric acid (GABA). One of the cake products is red velvet cake. The selection of red velvet cake products in the final project aims to: 1) Determine the standard red velvet cake recipe with the substitution of brown rice flour, 2) determine the community’s acceptance of red velvet cake products with the substitution of brown rice flour. The type of research used in making this product is Reaserch and Development (R & D) with a 4D development model (Define, Design, Develop, Disseminate). The results obtained from the research of this product are the right recipe for Red Velvet Cake products. Red Rice Flour Substitution is a product with a percentage of 30% brown rice flour and 70% wheat flour and this product also has nutritional value information to show that the product is acceptable by the community . Keywords: red velvet cake, brown rice and dietary fiber.